Pengaruh Kemiringan Sudut Kontak Drive Pulley Continuously Variable Transmission (CVT) Standar dan Modifikasi pada Sepeda Motor Yamaha SOUL GT Terhadap Keluaran Daya - Joko Waluyo (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2021)
Research titled Effect of puley continioly variable Transmision (CVT) standard and modivikasi drive contact angle on Yamaha SOUL GT 155 CC motorcycle on power output, the purpose of this study is to determine the effect of the most maximum changes in power and torque His research method is experimentally conducting his research at Karbu Racing Jogja GG. Tutul 2 No.80, Papringan, Caturtunggal, Kecamatan, Depok Sleman, Special Region of Yogyakarta tools used dyno test and tacho meter. The results of the study obtained that the power and torque for pully with modivikasi 13 0 has a greater value when compared to the standard pulley 140. The results resulted in a modivikasi pulley of 130 power and a maximum torque of 7.87 HP and 14.94 Newton meters at a rotation of 3250 RPM. So it can be concluded that pulley modivikasi 130 is very suitable when used for motor racing. Keywords : pulley 130, pully 140 , Torque, power, motor racing